Creating a Novel Graphene Oxide/Iron/Polylactic Acid Composite that Promotes Dental Pulp Stem Cell Proliferation and Mineralization. (16th April 2018) - Isseroff, Rebecca; Chen, John; Khan, Zaiff; Guha, Anoushka; Lin, Simon; Li, Juyi; Fang, Kuan-che; Zhang, Linxi; Simon, Marcia; Rafailovich, Miriam
ABSTRACT: Dental pulp stem cells (DPSCs) can differentiate into bone cells when provided the correct environment, potentially generating cells to repair non-union fractures. Polylactic Acid (PLA) is a biocompatible polymer for 3-D printing of scaffolds, but DPSCs do not proliferate well on PLA. With the goal of making PLA more conducive for DPSC growth, Graphene Oxide (GO); partially reduced Graphene Oxide (pRGO); GO with iron nanoparticles (FeGO) or Fe-pRGO were incorporated into PLA and spun cast as thin films onto silicon wafers for DPSC plating. DPSCs on Fe-pRGO displayed the fastest doubling time and the highest cell modulus; Fe-pRGO with exterior magnets produced high cell density. SEM demonstrated DPSC mineralization, whereas PLA-only DPSC cultures showed none. Results suggest that PLA/Fe-pRGO and PLA/pRGO enhance DPSC proliferation and possibly differentiation with the potential for use as a 3-D printed scaffold for tissue engineering.